Application of the approximation method in the algorithm for determining the position of a geostationary satellite - Калманова , Д. М.; Ашуров , А. Е.; Рахимова, А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article is devoted to the study of the features of the movement of geostationary satellites. The relevance lies in the possibility of more accurate determination of the position of the geostationary spacecraft for the correct performance of target tasks, as well as to increase the efficiency and improve the performance of satellites. The issues of using non-singular elements are considered to determine the satellite position in detail. Non-singular elements solve the problem of increasing the approximation error at very small values of eccentricity and inclination. As a result of the work performed, a program code and an algorithm were drawn up for calculating coordinates, a velocity vector and modeling the movement of a geostationary satellite at any time. The application of the results of the program code will make it possible to determine with high accuracy and further simulate the satellite’s orbital movement, which will lead to a decrease in dangerous situations in near-earth space. The topic under consideration will be of interest to specialists studying the issues of spacecraft ballistics.